The heterochromatic copies of the LTR retrotransposons as a record of the genomic events that have shaped the Drosophila melanogaster genome. - Mugnier, N.; Gueguen, L.; Vieira, C.; Biémont, C. (Gene, 2008)
Transposable elements, which are major components of most genomes, are known to accumulate in heterochromatic regions in which they have progressively diverged in sequence by mutations and internal deletions and insertions (indels) during the course of evolution. They therefore provide a record of the genomic events that have shaped the genomes, some of which could correspond to speciation events. Using the sequence divergence between the long terminal repeats (LTRs), we estimated the date of the insertion events of the LTR retrotransposon copies embedded within the heterochromatin regions of the Drosophila melanogaster genome. We did not detect traces of any specific waves of mobilization of retrotransposons within heterochromatin, apart from a very recent wave, which corresponds to the numerous LTR retrotransposon copies found in euchromatin.